Technology of Textile Materials and Initial Treatment of Raw Materials - Alisher, Xamidov (European Journal of Life Safety and Stability (2660-9630), 2022)
The creation of fire-resistant textile materials obtained on the basis of grafted copolymers, the improvement of physic-chemical and fire-technical properties.